2008
DOI: 10.1093/cvr/cvn158
|View full text |Cite
|
Sign up to set email alerts
|

Rho-GDP dissociation inhibitor alpha downregulated by low shear stress promotes vascular smooth muscle cell migration and apoptosis: a proteomic analysis

Abstract: The results indicate that the LSS-induced VSMC migration and apoptosis are mediated by a downregulation of Rho-GDIalpha. The effect of Rho-GDIalpha on VSMC migration is mediated by the PI3K/Akt pathway, but its effect on VSMC apoptosis is not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 34 publications
5
60
0
1
Order By: Relevance
“…On the contrary, the low shear stress induces VSMC proliferation [20,23]. Similar results are also observed in tissue culture studies [24][25][26][27], hence the low shear stress may act as a critical factor for intimal hyperplasia. Subnormal shear-stress-induced intimal thickening requires VSMC proliferation and migration [28], and it is well known that the mechanism of VSMC proliferation and migration regulated by shear stress involves platelet-derived growth factor (PDGF) [29] and matrix metalloproteinase-2 (MMP-2) through nitric oxide (NO) signalling pathway [30,31].…”
Section: Haemodynamic Factors and Vascular Smoothsupporting
confidence: 62%
“…On the contrary, the low shear stress induces VSMC proliferation [20,23]. Similar results are also observed in tissue culture studies [24][25][26][27], hence the low shear stress may act as a critical factor for intimal hyperplasia. Subnormal shear-stress-induced intimal thickening requires VSMC proliferation and migration [28], and it is well known that the mechanism of VSMC proliferation and migration regulated by shear stress involves platelet-derived growth factor (PDGF) [29] and matrix metalloproteinase-2 (MMP-2) through nitric oxide (NO) signalling pathway [30,31].…”
Section: Haemodynamic Factors and Vascular Smoothsupporting
confidence: 62%
“…Boulter et al recently described how GDI␣ depletion triggers degradation of Rho proteins and modifies melanoma cell migration (4). Qi et al also described how the simple reduction of GDI␣ expression can induce Rac1 activation and VSMC migration (35). These works and the present study highlight how GDFs are determinants of cell physiology.…”
Section: Discussionsupporting
confidence: 77%
“…There were 43 protein spots differentially expressed between NSS and LowSS cultured vessels (Table S1), among which eight proteins were highly expressed in vessels under NSS and 35 proteins were highly expressed in LowSS. Rho dissociation factor α, which was shown to regulate VSMC migration and apoptosis in our previous study (13), did show a lower expression in LowSS in the current study (Table S1), but was not included in the IPArevealed signaling network because it did not pass the significance level of P < 0.05 ( Fig. 2 and Table S2).…”
Section: Resultsmentioning
confidence: 67%
“…Growing evidence, both in vivo and in vitro, has revealed that the essential pathology of vascular remodeling during atherosclerosis induced by low and oscillating shear stresses involves the proliferation, apoptosis, migration, and phenotype transformation of VSMCs (2,13,14). As ECs are directly exposed to shear stress, understanding of their crosstalk with VSMCs under shear flow can help to elucidate the molecular mechanism of the vascular remodeling induced by low shear stress (LowSS).…”
mentioning
confidence: 99%